Desa Grogol dengan Potensi Perkembangannya - Santosa, Kurnia Richard; Pramana, Isidorus Risang Tanaya Deva; Alfyanti, Maria Veronica Amara; Surbakti, Yemima Apriesti Dameria; Saputra, Justyn Rudes; Warang, Florentinus Valeri; Febriana, Agata Nadia; Widi, Dionysius Nova Sesoco; Septiari, Ni Luh Putu Karina; Nugraha, Geraldus Harry; Widiastiani, Nindry Sulistya (Jurnal Atma Inovasia, 2021)
KKN 78 UAJY or KKN Society 5.0. using online method, so there is no direct contact with people who live in the village. Group 40 located in Grogol Village, Paliyan, Special Region of Yogyakarta. This village has a potential in tourism sector. This program aim to help Grogol Village for their development, support, and manage their potential resource. This KKN program using literature review method based on trusted source from internet, personal experience, and interview with the expert. The result of this method give us the information and idea that can relate with the situation of Grogol Village. The result is develop the tourism sector by build the tourist object such as Nature learning program using the human resource in Grogol because most of them are farmers, the second is build the outbond area using the forest or not used land, the third is build the rafting zone or develop the water travel, and the fourth is build the Culture Center because Yogyakarta is the city with strong Java Culture and Grogol is located in Gunungkidul that has a lot of tourist attraction, and the fifth is team up with the tour agency in purpose to introduce the Grogol Village to people inside or outside of Yogyakarta so they are interested to come to Grogol Village. Beside tourism, Grogol village can develop the shallot cultivation because shallot doesn’t need too much water and the climate and land condition is potential for shallot cultivation.